2006
DOI: 10.1139/x06-019
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mineralization in short-rotation tree plantations along a soil nitrogen gradient

Abstract: We measured soil nitrogen (N) mineralization along an N fertilization gradient (control; irrigation only (I + 0 N); irrigation with 56 (I + 56 N), 112 (I + 112 N), and 224 (I + 224 N) kg N·ha–1·year–1, respectively) in 7-year-old cottonwood (Populus deltoides Marsh.), cherrybark oak (Quercus falcata Michx. var. pagodifolia Ell.), American sycamore (Platanus occidentalis L.), and loblolly pine (Pinus taeda L.) plantations established on a well-drained Redbay sandy loam (a fine loamy, siliceous, thermic Rhodic P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
5
15
1
Order By: Relevance
“…Calculating the proportion of fertilizer N acquired, or FUE, requires quantification of N AV based on both the amount of N applied via fertilization and N MIN . Although the actual amount of N MIN was unknown, the use of paired fertilized and non-fertilized plot N UP provided approximations of N MIN rates that are comparable to those found by others in the region (Lee and Jose 2006;Gurlevik et al 2004). Mineralization following fertilization can be higher (Connell et al 1995) or lower (Johnson et al 1980), and can depend on the forest type (Lee and Jose 2006), so the magnitude of mineralized N available in fertilized plots was only approximated and some inconsistencies exist.…”
Section: Indices and Strategies Of Efficiencysupporting
confidence: 62%
See 1 more Smart Citation
“…Calculating the proportion of fertilizer N acquired, or FUE, requires quantification of N AV based on both the amount of N applied via fertilization and N MIN . Although the actual amount of N MIN was unknown, the use of paired fertilized and non-fertilized plot N UP provided approximations of N MIN rates that are comparable to those found by others in the region (Lee and Jose 2006;Gurlevik et al 2004). Mineralization following fertilization can be higher (Connell et al 1995) or lower (Johnson et al 1980), and can depend on the forest type (Lee and Jose 2006), so the magnitude of mineralized N available in fertilized plots was only approximated and some inconsistencies exist.…”
Section: Indices and Strategies Of Efficiencysupporting
confidence: 62%
“…Although the actual amount of N MIN was unknown, the use of paired fertilized and non-fertilized plot N UP provided approximations of N MIN rates that are comparable to those found by others in the region (Lee and Jose 2006;Gurlevik et al 2004). Mineralization following fertilization can be higher (Connell et al 1995) or lower (Johnson et al 1980), and can depend on the forest type (Lee and Jose 2006), so the magnitude of mineralized N available in fertilized plots was only approximated and some inconsistencies exist. Both N UP and NPP were positively influenced by irrigation, but the lack of an irrigation effect on FUE suggests that, although more N may have been available with irrigation, the amount that could be acquired was not influenced.…”
Section: Indices and Strategies Of Efficiencysupporting
confidence: 62%
“…The 81 kg·ha −1 annual Nmin mean of the CONTROL treatment in this study was similar to the 75 kg·ha −1 annual Nmin reported for a 7-year-old loblolly pine plantation in Florida, USA on sandy loam soil [33]. The 81 to 146 kg·ha −1 annual Nmin range of this study was somewhat higher than the 22 to 96 kg·ha −1 annual Nmin range for a 14-year-old loblolly pine plantation in North Carolina, USA on a highly weathered, eroded clay loam receiving fertilizer and herbicide [2].…”
Section: Discussionsupporting
confidence: 83%
“…The increases in soil NO3-N and the NO3:exchangeable N ratio at the Lucky site and the increases in soil NO3-N at the Dodson in response to FERTVS treatment conducted post-thinning suggest that this treatment exceeded stand N demand. These results show that avoiding fertilization preor post-thinning at an N-sufficient site and applying herbicide in the year of thinning and fertilization at the range of site conditions in this study could minimize NO3-N concentration increases, which can help in reducing N leaching loss potential and improving fertilizer use efficiency [33].…”
Section: Discussionmentioning
confidence: 74%
“…The measured annual N mineralization (280 kg N ha À1 yr À1 ) was much higher than N fertilization in 2002 but part of this mineralized N may have been derived from previous microbial immobilisation of chemical N fertilizer. Positive fertilizer-mineralization interactions were reported by Kolberg et al (1999) for cropping systems and by Lee and Jose (2006) for tree plantations. The method used, although adequate to compare adjacent plots, may over-estimate absolute values because roots are cut (Jussy et al 2004).…”
Section: N Dynamicsmentioning
confidence: 92%